Permainan Edukatif Papan Pencocokan Warna dan Bentuk Berpengaruh Terhadap Perkembangan Kognitif Pada Anak Usia Dini - Ignasia Yunita Sari; Annisa Azhara (Caring : Jurnal Keperawatan, 2025)
Early childhood is a child aged 3-6 years. As many as 88,923 children, who experience delays in cognitive development as much as 21.5%, so it is necessary to provide stimulation. One of the media used to stimulate children's cognitive development is an educational game tool for matching colors and shapes.To determine the influence of educational board games for matching colors and shapes on cognitive development in early childhood.This research design uses a pre-experimental design with a one group pre-test and post-test without control approach using probability sampling with a total sampling of 35 respondents aged 3-4 years. The measuring instrument is an observation sheet. Analysis using the Wilcoxon signed rank test. Shows the respondents with the most gender, namely women with a total of 23 respondents, the most age is 4 years with a total of 23 respondents. The Kolmogorov-Smirnov normality test obtained a result of p = 0.000 (p <0.05) not normally distributed so using the Wilcoxon signed rank test, the p-value result was (0.000) which can be interpreted as p-value <0.05 there is a strong influence accepted.There is an influence of educational board games for matching colors and shapes on cognitive development in early childhood